A characteristics study on the heavy metals (Pb, Zn, As) in the coal of Southwest China. (April 2015) - Yu, L.; Li, D. W.
<x content-type="archive" xml:space="preserve">Abstract</x> In this paper the concentration distribution of lead (Pb), arsenic (As) and zinc (Zn) in seven coal samples taken from Southwest China were analysed by applying the sequential extraction method. The results showed that the total concentrations of these trace elements in different samples varied significantly, as did their distribution within some specific fractions. The highest percentages of these three elements are contained in the exchangeable and sulphide-bound fractions, which tend to be released into the atmosphere and therefore pose a threat to the environment and human health because of their high mobility and toxicity. The As concentration in the exchangeable fraction was only as high as 19·07 mg kg−1 in the Shuikuang sample, while in the other samples it was below the detection limit. The concentration in the sulphide-bound fraction accounted for 55·26%; thereby indicating a large amount of pyrite because of its sulphophile affinity. Most fractions of As and Zn were contained in the residual fraction.